DEVELOPMENT OF METAVERS CLASSROOM WITH COLLABORATIVE LEARNING CONCEPT ON THE CREATION OF 3D INFOGRAPHIC TO ENHANCE CREATIVE THINKING SKILLS FOR MATAYOMSUKSA 4TH STUDENTS - Onsomkrit, Sunisa; Rampai , Nattaphon; Plangsorn, Boonrat (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article is a research about the to develop of metaverse classroom in conjunction with the concept of collaborative learning on 3D infographics that enhance creative thinking skills for Matayomsuksa 4th students The objectives of this research are as follows: 1) to develop a to develop of metaverse with collaborative learning concepts; 1) To be of appropriate quality and efficiency according to the 80/80 criteria. 2) To compare the pre-and post-study academic achievements of students taught in a to develop of metaverse with collaborative learning concepts. 3) To compare students' creative thinking skills. between groups studying in a to develop of metaverse with collaborative learning concepts and groups studying in a traditional classroom, and 4) To study student satisfaction. The target group used in this research is 40 Matayomsuksa 4th students, semester 1, academic year 2023, using a cluster sampling. It is experimental research. There are tools used in research. 1) Develop of Metaverse classroom 2) Academic achievement test 3) Creative thinking skills assessment 4) Satisfaction assessment and statistics used in data analysis include mean, standard deviation. The research results found that 1) Develop of Metaverse classroom with collaborative learning concept It has an efficiency of 80.23 / 81.75, which meets the specified criteria. 2) Students have academic achievements after studying. Teaching in a develop of metaverse combined with collaborative learning concepts had a higher average academic achievement after studying than before with the group studying in a develop of metaverse classroom. Statistically significant at the 0.05 level. 3) Students' creativity was higher in the group who studied in a develop of metaverse with collaborative learning concepts than in the group who studied in a traditional classroom. Statistically significant at the 0.05 level and 4) Students are satisfied with the development of the develop of metaverse with the collaborative learning concept. At a high level